Medical Image Compression using DCT and DWT Techniques - Hadi, Gulanar Mohammed (European Journal of Applied Sciences, 2015)
In this paper we used DCT ( Discrete Cosine Transform ) and DWT ( Discrete Wavelet Transform) to achieve optimal compression ratio for two types of medical images(CT scan and MRI) with keeping good quality of these images. In 2D- DCT; the image is broken up into blocks of n × m pixels (with n=m= 8 typically), and then 2D- DCT is used to produce a block of n × m DCT coefficients for each block of pixels, the result coefficients are quantized, which must result in lossy but highly efficient compression ratio . The important feature of the DCT the feature that makes it so useful in data compression, is that it takes correlated input data and concentrates its energy in just the first few transform coefficients. for the same images we used DWT method ,and then compare their results to choose the best method for compressing medical image with good quality. The compression algorithms programmed and tested to achieve the goal of reducing the file size (i.e, good compression ratio) using Matlab (R2008a).The conclusion part in this paper explain the results.